2008
DOI: 10.1080/07373930801946759
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Energy–Assisted Vacuum Drying of FreshEucalyptus globulus

Abstract: Worldwide, eucalyptus tree plantations have been established in appropriate climates because of fast growth and wood qualities suitable mainly for pulp. A potential exists of converting eucalyptus trees into lumber that may be of higher value than pulp. Conventional drying of lumber of Eucalyptus globulus is often difficult because of the occurrence of drying stresses, leading to collapse and checking. The special method of vacuum drying while heating the wood with high-frequency energy (75-77 mbar, 46-51 C) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, CKD has some drawbacks, such as a long drying cycle, high drying stress, and environmental pollution. Many scholars also use special drying methods to dry eucalypti, such as vacuum drying, microwave drying, freeze-drying, and solar drying [5][6][7][8]. Compared with the mentioned above drying methods, supercritical CO 2 drying (SCD) has the advantages of fast drying rate, environmental protection, and simple operation [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, CKD has some drawbacks, such as a long drying cycle, high drying stress, and environmental pollution. Many scholars also use special drying methods to dry eucalypti, such as vacuum drying, microwave drying, freeze-drying, and solar drying [5][6][7][8]. Compared with the mentioned above drying methods, supercritical CO 2 drying (SCD) has the advantages of fast drying rate, environmental protection, and simple operation [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is predicted, however, that the drying time can be further reduced by reducing the vacuum time. In their study, Hansmann et al (2008) have dried Eucalyptus Globulus, which has a high tendency to crack like oak in drying, at a low pressure (76 mbar) with a high frequency and dried from 58% to 10.3% moisture in 5 days. Considering that the rate of hourly drying (0.39%) they have obtained is higher than the values obtained in this study (0.22%) can be resulted due to working at lower pressures, it can be suggested that drying experiments at lower pressures can be made for oak lumber drying.…”
Section: Discussionmentioning
confidence: 99%
“…Hansmann et al [9] developed a technique to rapidly dry green Eucalyptus globulus with shorter drying times than conventional drying and with better quality (less cracks) [9]. Others have attempted to combine vacuum drying with different technologies to improve drying time and quality.…”
Section: Vacuum Dryingmentioning
confidence: 99%